RELATIONSHIP BETWEEN LENGTH OF STAY FOR REHABILITATION AND FUNCTIONAL OUTCOMES IN STROKE PATIENTS - Betül Çiftçi; Sevgi İkbali Afşar (MNJ (Malang Neurology Journal), 2023)
Background: The comorbidities, age and disability of the stroke patients may influence the rehabilitation period. In the rehabilitation process of stroke patients, the length of stay in hospital is important because of its economic and psychological effects. Objective: The purpose of this study was to evaluate whether there is a relationship between the length of hospital stay for rehabilitation and functional outcomes of stroke patients. Methods: The medical records of 97 patients who were admitted to a rehabilitation unit were analyzed retrospectively. The functional output, the level of spasticity, and motor development at admission and discharge were determined using the Functional Independence Measure instrument, the Modified Ashworth Scale, and the Brunnstrom test, respectively. Based on the length of hospital stay, patients were divided into two groups: hospital stays ≤ 3 months (Group 1) and > 3 months (Group 2). Clinical features and functional output were then compared between the groups. Results: The gain of Functional Independence Measure instrument -total and Functional Independence Measure instrument-motor scores were significantly higher in Group 1 (n=74) (p < 0.05) than Group 2 (n=23). The Modified Ashworth Scale scores of the upper extremities and of the lower extremities at admission and discharge were significantly higher in Group 2 (p < 0.05 for all). Conclusion: The findings of this study revealed that a prolonged length of hospital stay has no greater positive effect on improvement of functional outcomes and spasticity of stroke patients.